Knowing How to Brush Teeth for Class VI Students at SDN Milangasri 1 Magetan: Mengetahui Cara Menyikat Gigi Pada Siswa Kelas VI SDN Milangasri 1 Magetan - Dewi, Yanita (Poltekkes Kemenkes Surabaya, 2025)
Oral and dental health problems commonly experienced by children are dental caries. A large number of children express complaints about dental caries, a condition that, if severe, can have a detrimental effect on their overall well-being. The child will experience pain, discomfort, and may have difficulty eating and sleeping. Dental caries at school age results from a lack of knowledge about correct oral hygiene practices, including inadequate teeth cleaning techniques and schedules. The problem with this resat is that only 69.4% of class VI students at SDN Milangasri 1 Magetan in 2024 will experience caries, but UKGS activities have been carried out 100%. The aim of this research is to find out the correct tooth brushing technique for class VI students at SDN Milangasri 1 Magetan. This research method is descriptive. This research focused on a group of 49 grade VI students at SDN Milangasri 1 Magetan. Data collection was carried out through an observation process, using observation sheets as the main tool. The observation sheet was used as a data collection tool. The data analysis technique used is to present the results obtained from the observation sheet in table format. Research has found that brushing the labial, buccal, palatine and lingual teeth are all in the unfavorable category. However, brushing teeth in the occlusal area is included in the good category. Conclusion: The method for brushing the teeth of class VI children at SDN Milangasri 1 Magetan is considered adequate.